Optimal design of Anger camera for bremsstrahlung imaging: Monte Carlo evaluation. - Walrand, Stephan; Hesse, Michel; Wojcik, Randy; Lhommel, Renaud; Jamar, Francois (Frontiers in Oncology, 2014)
A conventional Anger camera is not adapted to bremsstrahlung imaging and, as a result, even using a reduced energy acquisition window, geometric x-rays represent less than 15% of the recorded events. This increases noise, limits the contrast, and reduces the quantification accuracy. Monte Carlo simulations of energy spectra showed that a camera based on a 30mm-thick BGO crystal and equipped with a high energy pinhole collimator is well adapted to bremsstrahlung imaging. The total scatter contamination is reduced by a factor ten versus a conventional NaI camera equipped with a high energy parallel hole collimator enabling acquisition using an extended energy window ranging from 50 to 350 keV. By using the recorded event energy in the reconstruction method, shorter acquisition time and reduced orbit range will be usable allowing the design of a simplified mobile gantry. This is more convenient for use in a busy catheterization room. After injecting a safe activity, a fast SPECT could be performed without moving the catheter tip in order to assess the liver dosimetry and estimate the additional safe activity that could still be injected. Further long running time Monte Carlo simulations of realistic acquisitions will allow assessing the quantification capability of such system. Simultaneously, a dedicated bremsstrahlung prototype camera reusing PMT-BGO blocks coming from a retired PET system is currently under design for further evaluation.